Understanding nutrient throughput of operational RAS farm effluents to support semi-commercial aquaponics: Easy upgrade possible beyond controversies - Lunda, Roman; Roy, Koushik; Másílko, Jan; Mráz, Jan (Journal of environmental management, 2019)
The present research attempted to address a key industry-level question amidst Recirculating Aquaculture System (RAS) waste throughput and aquaponics limitations controversies. Nutrient throughput of three operational RAS farms with progressive size proportions (16, 130, 1400 m3), aquaculture intensity (24, 62, 86 kg stock m-3) were studied. Results suggest - daily total efflux and potency of nutrients in effluents should not be generalized, extreme variability exists. Consistencies of nutrients in wastewater (except N, Ca and Na) are higher than in sludge. Asynchrony between patterns of nutrient loading and effluent nutrient concentrations exist for secondary macronutrients and micronutrients (S, Mg, Fe, Cu, Zn, B, Mo). Macronutrient output generally increases with increasing farm size and culture intensity but same cannot be said for micronutrients. Deficiency in wastewater can be completely masked using raw or mineralized sludge, usually containing 3-17 times higher nutrient concentrations. RAS effluents (wastewater and sludge combined) contain adequate N, P, Mg, Ca, S, Fe, Zn, Cu, Ni to meet most aquaponic crop needs. K is generally deficient requiring a full-fledged fertilization. Micronutrients B, Mo are partly sufficient and can be easily ameliorated by increasing sludge release. The presumption surrounding 'definite' phyto-toxic Na levels in RAS effluents should be reconsidered - practical solutions available too. No threat of heavy metal accumulation or discharge was observed. Most of the 'well-known' operational influences failed to show any significant predictable power in deciding nutrient throughput from RAS systems. Calibration of nutrient output from operational RAS farms may be primarily focused around six predictors we identified. Despite inherent complexity of effluents, the conversion of RAS farms to semi-commercial aquaponics should not be deterred by nutrient insufficiency or nutrient safety arguments. Incentivizing RAS farm wastes through semi-commercial aquaponics should be encouraged - sufficient and safe nutrients are available.
Keywords: odpadní voda; Farms; farmy; Modeling; Aquaponics; Aquaculture; Sustainability; Nutrient output; vodní hospodářství; živiny; Wastewater; Waste Water; Sewage; Recirculating aquaculture system; Waste recycling; Sludge; EU; Hydroponic plant cultivation; Nutrients; odpadní vody